Neural activation during processing of aversive faces predicts treatment outcome in alcoholism. (7th March 2013) - Charlet, Katrin; Schlagenhauf, Florian; Richter, Anne; Naundorf, Karina; Dornhof, Lina; Weinfurtner, Christopher E. J.; König, Friederike; Walaszek, Bernadeta; Schubert, Florian; Müller, Christian A.; Gutwinski, Stefan; Seissinger, Annette; et al.
Abstract Neuropsychological studies reported decoding deficits of emotional facial expressions in alcohol‐dependent patients, and imaging studies revealed reduced prefrontal and limbic activation during emotional face processing. However, it remains unclear whether this reduced neural activation is mediated by alcohol‐associated volume reductions and whether it interacts with treatment outcome. We combined analyses of neural activation during an aversive face‐cue‐comparison task and local gray matter volumes (GM) using Biological Parametric Mapping in 33 detoxified alcohol‐dependent patients and 33 matched healthy controls. Alcoholics displayed reduced activation toward aversive faces–neutral shapes in bilateral fusiform gyrus [FG; Brodmann areas (BA) 18/19], right middle frontal gyrus (BA46/47), right inferior parietal gyrus (BA7) and left cerebellum compared with controls, which were explained by GM differences (except for cerebellum). Enhanced functional activation in patients versus controls was found in left rostral anterior cingulate cortex (ACC) and medial frontal gyrus (BA10/11), even after GM reduction control. Increased ACC activation correlated significantly with less (previous) lifetime alcohol intake [Lifetime Drinking History (LDH)], longer abstinence and less subsequent binge drinking in patients. High LDH appear to impair treatment outcome via its neurotoxicity on ACC integrity. Thus, high activation of the rostral ACC elicited by affective faces appears to be a resilience factor predicting better treatment outcome. Although no group differences were found, increased FG activation correlated with patients' higher LDH. Because high LDH correlated with worse task performance for facial stimuli in patients, elevated activation in the fusiform 'face' area may reflect inefficient compensatory activation. Therapeutic interventions (e.g. emotion evaluation training) may enable patients to cope with social stress and to decrease relapses after detoxification.